2012
DOI: 10.1039/c2sm25223f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of molecular interactions between lipid membranes and ionic liquids using model cell membranes

Abstract: Ionic liquids (ILs) are often considered to be green solvents based on their unusual stability, although their toxicity to living organisms has become an emerging issue based on a number of recent studies. We assume that one of the main reasons for this high level of cell toxicity is the molecular interactions between ILs and cell membranes. In this study, we used model cells to demonstrate that ILs can incorporate into lipid membranes, resulting in the perturbation of membrane structure. We employed various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
91
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 27 publications
4
91
0
1
Order By: Relevance
“…Figure reproduced with permission from the publisher upon the absorption of RTIL cations, and (iv) Importance of the chemistry of the molecules (Weaver et al 2013;Gal et al 2012;Lee et al 2015). The effects of RTILs on the thermotropic behavior of biomembranes were also probed in several reports (Weaver et al 2013;Wang et al 2016;Jeong et al 2012. ) At low concentrations of RTILs, the variation of the main phase transition of phospholipids bilayers is negligible, and at high concentration the variation is of the order of 5 to 10 degrees, sometimes reaching 20 degrees, but this just before the collapse of the bilayers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure reproduced with permission from the publisher upon the absorption of RTIL cations, and (iv) Importance of the chemistry of the molecules (Weaver et al 2013;Gal et al 2012;Lee et al 2015). The effects of RTILs on the thermotropic behavior of biomembranes were also probed in several reports (Weaver et al 2013;Wang et al 2016;Jeong et al 2012. ) At low concentrations of RTILs, the variation of the main phase transition of phospholipids bilayers is negligible, and at high concentration the variation is of the order of 5 to 10 degrees, sometimes reaching 20 degrees, but this just before the collapse of the bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In Lim et al, for example, the mutual interaction between RTIL cations once absorbed into the membrane has been studied, and the measured increment of permeability due to the absorption of RTILs has been related to their antibacterial activity. Investigations focused on specific cases and more complex systems, moreover, have enriched even more the broad and diverse panorama presented above (Patel et al 2016;Modi et al 2011;Jeong et al 2012;Ryu et al 2015;Lee et al 2015). An interesting example is the study of Jeon, Lee and co-workers on the effect of RTILs on the ion channel function of Gramicidin A embedded in a phospholipid bilayer (Jeong et al 2012;Ryu et al 2015;Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans showed that imidazolium-based ILs with longer hydrocarbon tails more significantly destabilize liposomes and supported lipid bilayers [21][22][23]. Jeong et al also showed that longer ILs at higher concentrations more effectively insert into membranes, which induces membrane instability, leading to the lower transition temperature of membranes [24]. Galluzzi et al found that the surfactant -monolayer interaction can be modulated by the ILtail length rather than by the electrostatic interactions between headgroups of ILs and lipids [25].…”
Section: Introductionmentioning
confidence: 96%